2021
DOI: 10.15252/emmm.202114544
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a conserved vulnerability site in SARS‐CoV‐2 by a human antibody

Abstract: An essential step for SARS-CoV-2 infection is the attachment to the host cell receptor by its Spike receptor-binding domain (RBD). Most of the existing RBD-targeting neutralizing antibodies block the receptor-binding motif (RBM), a mutable region with the potential to generate neutralization escape mutants. Here, we isolated and structurally characterized a non-RBMtargeting monoclonal antibody (FD20) from convalescent patients. FD20 engages the RBD at an epitope distal to the RBM with a K D of 5.6 nM, neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 93 publications
4
29
1
Order By: Relevance
“…Three rounds of solution panning were performed with increasingly stringent conditions and an off-selection step to screen high-affinity nanobodies. Subsequent screening using ELISA and fluorescence-detection size exclusion chromatography (FSEC; Li et al, 2021a , b ) identified binders with ELISA signal that is at least three times higher than a control nanobody, as well as the ability to shift the gel filtration peak of fluorescently labeled RBD at 0.5 μM ( Figure 1A ). We identified 28 unique clones as positive clones and we focus on DL28 for this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three rounds of solution panning were performed with increasingly stringent conditions and an off-selection step to screen high-affinity nanobodies. Subsequent screening using ELISA and fluorescence-detection size exclusion chromatography (FSEC; Li et al, 2021a , b ) identified binders with ELISA signal that is at least three times higher than a control nanobody, as well as the ability to shift the gel filtration peak of fluorescently labeled RBD at 0.5 μM ( Figure 1A ). We identified 28 unique clones as positive clones and we focus on DL28 for this study.…”
Section: Resultsmentioning
confidence: 99%
“…Due to high demands and limited BSL3 laboratory resources during the continuing outbreak, the neutralization activity of DL28 against the authentic SARS-CoV-2 and the VOCs were not tested in this study. However, accumulating evidence from publications in this field since early 2020 has highlighted a strong correlation between assays using pseudovirus and authentic virus (Bewley et al, 2021 ; Jones et al, 2021 ; Li et al, 2021a , b ). Thus, it is likely that DL28 would neutralize the authentic viruses too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has suggested a general pattern regarding antibody characteristics and epitope. RBM-targeting antibodies are generally more potent than those targeting the RBD core [ 9 , [63] , [64] , [65] ] but are more susceptible to escape mutants [ 64 , [66] , [67] , [68] , [69] , [70] ]. Consistent with this trend, despite DL4's resistance to the mutations in the Alpha strain, its neutralizing activity is compromised or fully lost against variants with more RBM mutations.…”
Section: Discussionmentioning
confidence: 99%
“…S assembles into a trimer and is heavily decorated by glycosylation to escape immune surveillance. Suiting the role of molecular recognition, the RBD is relatively less glycosylated and therefore represents a hot spot for neutralizing antibodies [ [5] , [6] , [7] , [8] , [9] , [10] , [11] ] and vaccine development [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. Much of the RBD and the receptor-binding motif (RBM, the ACE2-binding surface) are shielded by the N-terminal domain of S1 from adjacent protomers of the S trimer in the so-called more stable “closed conformation”; and such RBDs are referred to as “down”-RBD.…”
Section: Introductionmentioning
confidence: 99%